Burden of illness for patients with primary biliary cholangitis: an observational study of clinical characteristics and healthcare resource utilization - Robert G Gish; Joanna P MacEwan; Alina Levine; Dannielle Lebovitch; Leona Bessonova; Darren Wheeler; Radhika Nair; Alan Bonder (Journal of Comparative Effectiveness Research)
Aim: To evaluate the clinical characteristics and healthcare resource utilization for acute care and its costs for patients with primary biliary cholangitis (PBC) with or without cirrhosis. Materials & methods: This retrospective observational cohort study was conducted using two datasets (Komodo’s Healthcare Map™ [Komodo Health] and Optum Clinformatics Data Mart [CDM] database) between 2015 and 2023. Patients (≥18 years) with PBC were identified based on ≥1 inpatient or ≥2 outpatient claims. Healthcare resource utilization for acute care (hospitalizations and emergency department [ED] visits [not leading to hospitalization]) were assessed in both datasets, and associated medical costs were evaluated in Optum CDM. Results: In Komodo Health, of the 29,758 patients with PBC (mean age: 59.2 years), 21.6% had cirrhosis and 50.4% of patients with cirrhosis had Medicaid or Medicare coverage. Of the total 8143 patients in Optum CDM (mean age: 67.0 years), 20.7% had cirrhosis, and most were enrolled in Medicare (69.7%). There was a larger proportion of men in the cirrhosis group compared with the no-cirrhosis group in Komodo Health (31.7 vs 16.3%) and Optum CDM (29.7 vs 16.5%). Annually, among patients with cirrhosis who had a hospitalization, 69.3% had additional hospitalizations, and among patients who had an ED visit, 52.9% had additional ED visits in Komodo Health; similar results were observed in Optum CDM. Among patients with at least one acute-care event, the mean annual acute-care costs with and without cirrhosis were $113,568 and $47,436, respectively. Conclusion: Data from two large healthcare claims databases showed that the majority of patients who had at least one acute-care event experienced additional acute-care events, particularly among those with cirrhosis. Timely treatment to avoid hospitalization and disease progression may help mitigate the clinical and economic burden for patients with PBC.